LEXICAL AND GRAMATICAL ERROR ON STUDENTS’ TRANSLATION FROM INDONESIAN TEXT TO ENGLISH TEXT - Nanik Retnowati (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2019)
Knowledge about what the learners’ know is part of teaching process, since the knowledge would be the clue for teachers in designing lesson material as well as method. Error analysis then becomes a common practice for language teachers to elicit what the learners have acquired.Translation is a kind of language skill which requires both linguistic and non linguistic knowledge.Thus studying students’ language used in their translation would be beneficial for teachers. This study is aimed at finding error on the students’ translation. This finding should give a description about the students’ obstacles in translation process.The writer took randomly ten ( 10 ) translation result of the students at English Education Program of FKIP UIKA Bogor as the sample data. Error analysis procedure is used; i.e. identifying, describing, explaining, and finding the cause of the error. The study found that students made some lexical errors such as miss spelling and inappropriate word choice. This is assumed to be caused by students’ lack of knowledge on spelling, word formation, word equivalence, and different point of view in Indonesian and English expressions. The grammatical error found are the use of affixes, verb, word order, and auxiliaries. The practice of omitting and adding was also found. Some shows the students’ effort to avoid the word due to their difficulties in putting the correct word in the construction. Others show that they are trying to use translation strategy, i.e.modulation to anticipate the difficulties in having literal translation. All findings should give an illustration that students need to be equipped more with the knowledge about how both source and target language operate to express meaning.